ANTECEDENTS OF ONLINE OJEK CUSTOMER LOYALTY (CASE STUDY OF STUDENT CUSTOMERS GO-JEK MEDAN) - Imelda Sitinjak; Martin Luter Purba (Journal of Management and Business, 2019)
This research is conducted to determine the level of customer loyalty influenced by the antecedents of customer satisfaction, the reasonableness of the price and quality of service, either directly or through customer satisfaction Go-Ride students in Medan. The unit of analysis of this study was individuals, namely female students from universities in Medan who had used Go-Ride. The method of determining the sample used purposive sampling method. Of the 298 data collected, 290 data were used as research samples and processed using the Lisrel 8.72 program. This research tests the quality of services with service quality indicators of a mass transport from the European Committee for Standardization which has never been used for motorcycle taxis. This study found that there is direct effect of antecedents of customer loyalty such as customer satisfaction and fairness of significant prices on Go-Ride student loyalty in Medan, while service quality has a significant indirect effect on Go-Ride student loyalty in Medan. This research has implications for a business start-up that must pay attention to the antecedents of loyalty, including customer satisfaction, fairness of price, and quality of service, and competitiveness will determine the sustainability of a start-up business because customers with businesses and businesses with businesses have mutually related relationships influence.